Early-Life Microbiome and Neurodevelopmental Disorders: A Systematic Review and Meta-Analysis - Fakruddin, Md.; Amin, Tasbir; Shishir, Md. Asaduzzaman; Jameel, Rameesa Maliha; Bari, Mubashshir Muntaha; Shameem, Nashia Farzana; Hossain, Amana; Jerin, Nusrat; Mannan, Shahnewaj Bin; Jime, Jinath Sultana; Bulbul, Nayeema (Current Neuropharmacology, 2026)
Background and ObjectivesThis systematic review intends to find out how neurodevelopmental disorders, including Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD), are influenced by the gut microbiota throughout early childhood. The study looks at the variety and types of microbes that a child is exposed to, the particular microbiome profiles associated with neurodevelopmental outcomes, and the molecular processes that underlie these relationships.MethodsWe performed a thorough search of PubMed, Scopus, the WHO Global Health Library (GHL), and ISI Web of Science. After screening 2,744 original studies based on predetermined eligibility criteria, 19 studies were included. Microbial groupings, presence (high/low), and related neurodevelopmental disorders were among the primary areas of data extraction. The methodological quality of the studies was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS).ResultsThe investigated literature repeatedly showed a strong correlation between dysbiosis of the gut microbiota and neurodevelopmental disorders. Cases of ASD were associated with both a high number of Clostridium species and a low number of Bifidobacterium species. On the other hand, a Low number of E. coli and a high number of the class Clostridia, phylum Firmicute, genus Bifidobacterium, and Akkermansia, as well as the species Listeria monocytogenes, Toxoplasma gondii, Streptococcus mutans, and Mycobacterium tuberculosis have been linked to ADHD. The NOS evaluation showed variation in the quality of the methodology; some studies had high scores, suggesting sound technique, while other studies had lower scores, indicating serious methodological flaws.ConclusionThe results highlight the potential impact of the gut microbiome throughout early life on neurodevelopmental outcomes, indicating that microbial imbalances may play a role in the onset of disorders like ASD and ADHD. However, to improve the quality of data, larger-scale longitudinal studies would be required.
Keywords: systematic review